Evaluation of Outages Based on the Saidi and Saifi Reliability Indices at PT. PLN (Persero) ULP Woha - Kamdanun Kamdanun; I Wayan Sukadana (Journal of World Science, 2026)
The reliability of the electricity distribution system is a key factor determining the quality of service provided to customers. In medium-voltage networks, disturbances caused by external factors, particularly animal-related interference, remain a significant challenge that contributes to increased System Average Interruption Frequency Index (SAIFI) and System Average Interruption Duration Index (SAIDI) values. This study aimed to evaluate the effectiveness of protective sleeve installation as a preventive measure for reducing feeder disturbances and improving distribution system reliability at PT PLN (Persero) ULP Woha. A quantitative descriptive approach was employed by analyzing and comparing disturbance data before and after protective sleeve installation during the 2024–2025 period. The findings revealed a significant reduction in the frequency and duration of disturbances following the installation of protective sleeves. Correspondingly, the improved SAIFI and SAIDI values indicated enhanced operational reliability of the distribution system. The results demonstrated that protective sleeves provided a practical and cost-effective solution for mitigating animal-related disturbances in medium-voltage distribution networks. The implications of this study include recommendations for PT PLN to adopt protective sleeves as a standard mitigation measure for animal-related disturbances across various customer service units and to support the development of more effective distribution network maintenance strategies.